2017
DOI: 10.1089/vbz.2016.2025
|View full text |Cite
|
Sign up to set email alerts
|

Yersiniaspp. in Wild Rodents and Shrews in Finland

Abstract: Yersinia enterocolitica and Yersinia pseudotuberculosis are important zoonotic bacteria causing human enteric yersiniosis commonly reported in Europe. All Y. pseudotuberculosis strains are considered pathogenic, while Y. enterocolitica include both pathogenic and nonpathogenic strains which can be divided into six biotypes (1A, 1B, and 2-5) and about 30 serotypes. The most common types causing yersiniosis in Europe are Y. enterocolitica bioserotypes 4/O:3 and 2/O:9. Strains belonging to biotype 1A are consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…For pathogenicity, pYV-encoded targets, such as yadA and virF, and chromosomal target genes ail and ystA are widely used (19,20,36,51,64). Species-specific regions of virulence genes have also been used for correct identification of enteropathogenic Yersinia (29). The new ISO method uses ail PCR to identify pathogenic Y. enterocolitica on selective agar plates before further confirmation (18).…”
Section: Identification Of Yersinia Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…For pathogenicity, pYV-encoded targets, such as yadA and virF, and chromosomal target genes ail and ystA are widely used (19,20,36,51,64). Species-specific regions of virulence genes have also been used for correct identification of enteropathogenic Yersinia (29). The new ISO method uses ail PCR to identify pathogenic Y. enterocolitica on selective agar plates before further confirmation (18).…”
Section: Identification Of Yersinia Sppmentioning
confidence: 99%
“…The new ISO method uses ail PCR to identify pathogenic Y. enterocolitica on selective agar plates before further confirmation (18). However, ail has frequently been detected in Y. enterocolitica biotype 1A strains isolated from wildlife, but also recently in lettuce, and this gene should therefore not be used alone in PCR detection when searching for pathogenic strains (28,29,31). (Table 2).…”
Section: Identification Of Yersinia Sppmentioning
confidence: 99%
“…hibernica isolates shows that all sequenced isolates share this deletion. Indeed, sucrose-negative Y. enterocolitica- like isolates have been reported from environmental sources [46] but without sequencing [8] and since the 16S rRNA gene for Y. enterocolitica and Y.…”
Section: Resultsmentioning
confidence: 99%
“…Improvement of the protocol for the cultural detection of Y. pseudotuberculosis. Although cold enrichment in conjunction with alkaline treatment (20 s in 0.25% or 0.5% potassium hydroxide [KOH] solution) has been used in several prevalence studies on Y. pseudotuberculosis (11,(25)(26)(27), some authors reported an increased susceptibility of this species to KOH (28)(29)(30). We analyzed the KOH susceptibility of seven strains belonging to five serotypes (O:1a, O:1b, O:3, O:4, and O:5), some of which are the most common serotypes in Europe (31).…”
Section: Resultsmentioning
confidence: 99%